STRATEGI ASESMEN DAN EVALUASI PEMBELAJARAN DI SEKOLAH DASAR - Intan Khoirun Nisa; Ellianawati; Barokah Isdaryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe assessment and evaluation strategies in primary schools that support the improvement of learning quality and student outcomes. The main issue addressed is the suboptimal implementation of comprehensive and contextual assessment practices, where many teachers still rely heavily on written tests and have not fully integrated formative, diagnostic, or authentic assessments. This research employed a qualitative descriptive approach through a literature review method. Data were collected from relevant national and international scholarly sources published between 2020 and 2025, and analyzed through data reduction, thematic presentation, and conclusion drawing. The findings reveal that effective assessment strategies include the use of various assessment types (diagnostic, formative, and summative), techniques (observation, performance assessment, written tests, interviews, reflective journals, portfolios), and the integration of technology such as online quizzes, digital assignment submissions, and e-portfolios. These strategies support active, reflective, and student-centered learning. However, their implementation faces several challenges, including limited teacher understanding, administrative burdens, and varying levels of student readiness. Proposed solutions involve continuous professional development, the use of digital tools, and adaptive assessment approaches. This study contributes both practically and theoretically by offering insights into effective and sustainable assessment strategies to enhance the overall quality of primary education.